Characteristics of Interference Fluctuation of Different Types of Stray Currents on Pipelines - XU Chengwei, CHEN Ruirui, ZHANG Rong, XIA Liang, LAN Wei, BI Wuxi (Cailiao Baohu)
AC/DC stray current interference corrosion has become one of the main causes of pipeline failure and damage， which seriously threatens the safety of pipeline operation.In order to understand the characteristics of different AC-DC stray current interference sources and their influence on the cathodic protection parameters of pipelines， the coupon method was used to monitor the interference sources of different types in a gas pipeline for a long time.Based on the test results， the typical interference characteristics of 7 types of interference types， including AC and DC static interference， dynamic interference and statically dynamic complex interference， were analyzed and summarized.Meanwhile， for complex AC and DC mixed interference， the corresponding evaluation indexes， threshold ranges， criteria and recommended methods were proposed for personal safety， AC and DC mixed interference and valve chamber insulation facilities.The research results provide a basis for pipeline operators to quickly identify the types of stray current interference sources， formulate corresponding protective measures， and reduce the risk of pipeline corrosion caused by complex stray current interference.